Phonemes in continuous speech are better recognized in context than in isolation - Brown, Annemarie C.; Childers, Eva; Bowen, Elijah F. W.; Zuckerberg, Gabriel A.; Granger, Richard (Frontiers in Communication, 2022)
The contribution of context to phoneme perception is a subject of extensive study. In recent years, while the perception of phonemes in and out of context has become characterized as well understood, new studies have emerged to challenge prevailing wisdom. Findings derived from rigorously controlled stimuli have failed to hold up when tested against continuous or more naturalistic speech, and vowels produced in isolation have been shown to possess different frequencies than vowels in spontaneous speech. In the present study, we examine the effect of context on vowel recognition, via stimuli taken directly from natural continuous speech in an audiobook. All tested vowel sounds were better recognized with surrounding context than in isolation, affirming the resilience of findings from past studies.